Seismic performance of a structural concrete pile-wharf connection before and after retrofit. (April 2022) - Foltz, Raymond R.; LaFave, James M.; Lee, Deuckhang
Highlights: Seismic performance of PC pile-wharf connection with T-headed dowel was investigated. Various seismic loading protocols and realistic boundary conditions were considered. Excellent seismic performances of pile-wharf connection were confirmed. Simple and effective strengthening method was addressed to damaged specimen. Retrofitted connection showed higher stiffness and improved capacity. Abstract: A full-scale precast prestressed concrete (PC) pile-wharf specimen with a T-headed dowel bar connection detail was tested under realistic loading and boundary conditions. The testing program introduced several seismic loading protocols, which were determined from nonlinear dynamic analyses of a typical U.S. port structure subjected to ground motions for various hazard levels. Conventional reversed cyclic loading tests were also conducted on the pile-wharf connection, damaged by seismic loading protocols, before and after retrofit. The specimen showed excellent seismic performance in terms of both strength and ductility. It was confirmed that the lateral drift response of such a PC pile-wharf connection is largely governed by a rigid-body rocking mechanism, with spalling in the pile and deck near the joint region appearing to be a main cause of stiffness degradation. This study also considered a section enlargement technique as an efficient retrofitting method of pile-wharf connections in container port structures. The retrofitted pile-wharf connection (with prior seismic damage) showed higher stiffness and improved capacity, but its deformation capacity (ductility) was inevitably limited by previously accumulated damage along the precast pile (where no strengthening was applied).